Karakteristik Aspal Porus dengan Campuran Serat Bemban (Donax Canniformis) Terhadap Porositas, Void In Mixture, dan Marshall Quotient - Yoga Saputra; Asri Wiana Lika Zahara; Muhammad Alif Lazuardi; Nur Maeysya Saida Amada; Ninis Hadi Haryanti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
The need for additional materials to improve the quality of porous asphalt that is environmentally friendly, the natural fiber is the right component. Bemban is a typical South Kalimantan plant that has good properties as a mixture material. This research was conducted to identify the characteristics of bemban fiber as a porous asphalt mixture material and identify the characteristics of porous asphalt with bemban fiber mixture. The characteristics measurement of bemban fiber includes moisture content, cellulose content, and lignin content, making asphalt specimens with bemban fiber mixture using variations of 1, 2, and 3 (%W/W), and porous asphalt characterization including porosity, Marshall Quotient (MQ), and Void in the Mixtures (VIM) with the Australian Asphalt Pavement Association (AAPA) 2004 reference standard. The results show the characteristics of bemban fiber with NaOH treatment 30 minutes 28oC obtained moisture content 2.36, cellulose content 22.52, and lignin content 1.33 (%W/W) which was used as a porous asphalt mixture. Characteristics of porous asphalt with variations of bemban fiber obtained optimum porosity, MQ, VIM values at the addition of bemban fiber 1 (%W/W) and has met the specification parameters.